Community resilience to crime: A study of the 2011 Brisbane flood. Issue 3 (28th June 2022) - Wickes, Rebecca; Zahnow, Renee; Corcoran, Jonathan; Kimpton, Anthony
Abstract: Understanding and enhancing community resilience is a global priority as societies encounter a rising number of extreme weather events. Given that these events are typically both sudden and unexpected, community resilience is typically examined after the disaster so there can be no before and after comparisons. As such, the extent to which existing community capacities buffer the effects of a traumatic event remains largely unexamined and untested in the literature. Drawing on a longitudinal study of 148 Brisbane suburbs, we examine the key community processes associated with community resilience to the crime before and after the 2011 Brisbane floods. We introduce a novel disaster severity index to simultaneously capture the direct and indirect impacts of the flood and embed this measure within our modeling framework. Results from the models provide important insights for predisaster preparedness and postdisaster rebuilding and recovery. Highlights: Neighborhood adaptive capacities were resistant to the flood. The bespoke flood severity index was strongly associated with lower levels of resilience to property crime postevent. Pre‐event adaptive capacities did not lead to resilience to property crime postevent.